Banking Sector Performance and Economic Growth in ASEAN: Evidence from Dynamic Panel GMM Analysis - Ahmad Farabi (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2025)
This study analyses the influence of banking sector performance on economic growth in the ASEAN region using annual panel data from eight countries for the period 2000-2021. Using annual data and the World Bank's World Development Indicators and Global Financial Development Indicators, this study applies a dynamic panel approach using the Generalized Method of Moments (GMM) to address growth dynamics and potential endogeneity. This study positions banking performance as the primary variable, accompanied by several macroeconomic and institutional control variables. Empirical results indicate that banking sector performance has a positive and significant effect on economic growth, and remains consistent across various model specifications and robustness tests. Furthermore, the findings suggest that the impact of banking on growth is strengthened through investment and trade openness channels. Overall, this study emphasizes the importance of banking sector performance as a determinant of economic growth in ASEAN and emphasizes the importance of policies to strengthen the financial sector in supporting sustainable economic growth.